A stochastic forest simulator accurately describes variation in boreal forest structure across Quebec, Canada - Rebecca Banbury Morgan; Timothy Baker; Louis Duchesne; Emmanuel Gloor; Roel Brienen (Forest Ecology and Management, 2026)

Novel symbioses between reef fishes and serpulid polychaetes in the Caribbean Sea - Morgan F. Bennett-Smith; Elizabeth McNamee; Samantha Masih; Timothy Lis; Mason Murchison; Allison Cinelli; Toshith Bhaumik; Catheline Y. M. Froehlich; Anna DeLoach; Ned DeLoach; Ninon Martinez; Peter M. Buston; et al. (Symbiosis, 2026)

Availability of Chinook and sockeye salmon as prey to Cook Inlet beluga whales - Jordy Bernard; Bill Templin; Adam Reimer; Timothy McKinley; Kalin Kellie; Kate Lomac-MacNair; Megan Blees; Morgan Bender; Milo Adkison; Lori Polasek; Lori Quakenbush (Frontiers in Marine Science, 2026)
Cook Inlet beluga whales (CIBW) are an endangered population of toothed whales in southcentral Alaska that have not shown signs of recovery over the past two decades. Since the 1999 harvest moratorium, the number of whales in the population has remained relatively stable, with the 2022 estimate at 381 whales. Despite extensive research efforts since its Endangered Species Act listing in 2008, the mechanisms limiting population growth remain poorly understood. Recent studies suggest prey availability could be a significant factor limiting reproduction. This study provides information relating to CIBW prey availability and identifies mechanisms that may limit CIBW population growth. We developed a database containing decades of Cook Inlet fisheries data collected by the Alaska Department of Fish and Game. We used annual run size and fish size data to establish indices of Chinook ( Oncorhynchus tshawytscha) and sockeye salmon ( Oncorhynchus nerka ) availability within the Northern and Central Districts of Upper Cook Inlet. Data were not available to do the same for chum ( Oncorhynchus keta ), coho ( Oncorhynchus kisutch ), and pink salmon ( Oncorhynchus gorbuscha ) or for other important prey species, such as eulachon ( Thaleicthys pacificus ) and Pacific herring ( Clupea pallasii ), thus we focus on prey species Chinook and sockeye salmon. Here we summarize fisheries information archived in the database, estimate annual vital rates of CIBWs using an age-structured integrated population dynamics model, and correlate these vital rates to indices of prey availability (i.e., the annual biomass of select salmon runs based on available fisheries data). The biomass of Chinook salmon, the first species of salmon to arrive in Cook Inlet to spawn, declined significantly in the late 2000s. However, the biomass of other species, including sockeye salmon, has shown no clear trend since the 1980s. There were some indications that CIBW survival rates declined between 2005 and 2017, a period over which the biomass of Chinook and sockeye runs decreased in magnitude. However, it is not clear without additional information, such as a longer time series on CIBW survival rates and prey abundance, whether an increase in salmon availability would lead to an increase in CIBW population.

Assessing water security under climate change in the Mexico–Lerma–Cutzamala region through system dynamics modeling - Ravi Hanumantha; Morgan Ruelle; Varalakshmi S; Yelena Ogneva-Himmelberger; Marisa Mazari-Hiriart; Karen Frey; Timothy J. Downs (Sustainable Water Resources Management, 2026)

The dolphin FRESH protocol: visual Freshwater-Related Evaluation of Skin Health in free-ranging bottlenose dolphins (Tursiops spp.) - Kristi L. Fazioli; Christina N. Toms; Ryan Takeshita; Alyssa Quackenbush; Denise Greig; Teresa Rowles; Lori Schwacke; Kathleen Colegrove; Ruth Y. Ewing; Deborah Fauquier; Denise Boyd; Aaron Bouwkamp; et al. (Frontiers in Marine Science, 2026)
Exposure to freshwater is a pressing health issue for coastal bottlenose dolphins ( Tursiops spp.). Environmental changes, including increased precipitation events and coastal infrastructure projects, are altering salinity within estuarine systems. Consequently, understanding effects of freshwater exposure on dolphins and developing tools to evaluate related health conditions is urgent. To address this need, a group of veterinarians, pathologists, epidemiologists, natural resource managers, and field biologists convened to create a protocol to visually assess freshwater-related skin lesions in free-ranging bottlenose dolphins. The Dolphin FRESH (Freshwater-Related Evaluation of Skin Health) Protocol guides users without medical backgrounds to screen and evaluate photographs by focusing on the visual identification of three primary indicators of freshwater skin disease: Overgrowth, Target-like Lesions, and Light Discoloration. By determining presence of the primary indicators and scoring associated characteristics, FRESH provides users with a relative assessment of the severity of these skin anomalies, and metrics to track progressive changes. The Scoring Rubric performed well during systematic testing, with evaluators correctly identifying freshwater cases through recognition of primary indicators and with no significant differences in total severity scores between field biologists and medical experts. FRESH is an important step in advancing knowledge on the effects of salinity fluctuations on dolphin health. When applied to photo datasets over time, this tool will enable researchers and managers to evaluate progression and regression of freshwater skin disease, occurrence and effects of multiple exposures, and the relationship between freshwater exposure skin indicators and health and survival outcomes.

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Increasing ewe productivity - challenges of sheep stakeholders across Europe and Turkey - Bríd McClearn; Jean-Marc Gautier; Claire Morgan-Davies; Ignacia Beltrán de Heredia; Roberto Ruiz; Antonello Carta; Sezen Ocak Yetişgin; Dinu Gavojdian; Cathy M. Dwyer; Timothy W.J. Keady (Livestock Science, 2025)

Health benefits of traffic emissions controls in melbourne, Australia - Timothy B. Chaston; Steven Utembe; Jason Choi; Karthik Gopi; Cassandra Yuen; Luke Knibbs; Ivan C. Hanigan; Richard Broome; Sotiris Vardoulakis; Suzanne Mavoa; Geoffrey Morgan (Environmental Research, 2025)

The mortality burden attributable to PM2.5 and NO2 from all sources and traffic-related air pollution in Australia - Nicolas Borchers-Arriagada; Timothy B. Chaston; Geoffrey G. Morgan; Luke D. Knibbs; Fay H. Johnston (Environmental Research, 2025)

Artificial isopod burrows provide a refuge from desiccation for intertidal crustaceans - Ethan X. Roberts; Lexie Cepeda; Jack A. Morgan; Timothy M. Davidson (Journal of Experimental Marine Biology and Ecology, 2025)

Monitoring river flow status using low-cost wildlife camera and image segmentation artificial intelligence - Jie Bao; Yunxiang Chen; Lupita Renteria; Morgan Barnes; Brieanne Forbes; Sophia McKever; Amy Goldman; Timothy Scheibe; James Stegen (Environmental Modelling & Software, 2025)

Longleaf and shortleaf pine seedling fire tolerance is more sensitive to shade than encroaching hardwood species - John L. Willis; Ajay Sharma; Timothy M. Shearman; J. Morgan Varner; Justin McKeithen (Forest Ecology and Management, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Molecular shifts in dissolved organic matter along a burn severity continuum for common land cover types in the Pacific Northwest, USA - J. Alan Roebuck; Samantha Grieger; Morgan E. Barnes; Xia Gillespie; Kevin D. Bladon; John D. Bailey; Emily B. Graham; Rosalie Chu; William Kew; Timothy D. Scheibe; Allison N. Myers-Pigg (Science of The Total Environment, 2025)

Spatial patterns of valley network erosion on early Mars - Timothy A. Goudge; Alexander M. Morgan; Gaia Stucky de Quay; Caleb I. Fassett (Icarus, 2024)

Dynamic modeling studies of basin-scale pressure interference and CO2 plume evolution in multi-well geologic CO2 storage - Nur Wijaya; David Morgan; Derek Vikara; Timothy Grant; Guoxiang Liu (Gas Science and Engineering, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Probabilistic reaction norm reveals family‐related variation in the association between size, condition, and sexual maturation onset in Atlantic salmon ( Salmo salar ) - Morgan S. Brown; Roberto Carvalheiro; Richard S. Taylor; Wagdy Mekkawy; Timothy D. W. Luke; Lewis Rands; Damien Nieuwesteeg; Brad S. Evans; Nicholas M. Wade; Curtis E. Lind; Pollyanna E. Hilder (Journal of Fish Biology, 2024)
This study investigated the relationship between the size, condition, year class, family, and sexual maturity of Atlantic salmon ( Salmo salar ) using data collected in an aquaculture selective breeding programme. Males that were sexually mature at 2 years of age (maiden spawn) have, on average, greater fork length and condition factor ( K ) at 1 year of age than their immature counterparts. For every 10‐mm increase in fork length or 0.1 increase in K at 1 year of age, the odds of sexual maturity at 2 years of age increased by 1.48 or 1.22 times, respectively. Females that were sexually mature at 3 years of age (maiden spawn) have, on average, greater fork length and K at 2 years of age than their immature counterparts. For every 10‐mm increase in fork length or 0.1 increase in K at 2 years of age, the odds of sexual maturity at 3 years of age increased by 1.06 or 1.44 times, respectively. The family explained 34.93% of the variation in sexual maturity among 2‐year‐old males that was not attributable to the average effects of fork length and K at 1 year of age and year class. The proportion of variation in sexual maturity among 3‐year‐old females explained by the family could not be investigated. These findings suggest that the onset of sexual maturation in Atlantic salmon is conditional on performance (with respect to energy availability) surpassing a threshold, the magnitude of which can vary between families and is determined by a genetic component. This could support the application of genetic selection to promote or inhibit the onset of sexual maturation in farmed stocks.

Participation in collaborative fisheries research improves the perceptions of recreational anglers towards marine protected areas - Erin M. Johnston; Grant T. Waltz; Rosamaria Kosaka; Ellie M. Brauer; Shelby L. Ziegler; Erica T. Jarvis Mason; Hunter S. Glanz; Lauren Zaragoza; Allison N. Kellum; Rachel O. Brooks; Brice X. Semmens; Christopher J. Honeyman; et al. (Frontiers in Marine Science, 2024)
Collaborative fisheries research programs engage stakeholders in data collection efforts, often with the benefit of increasing transparency about the status and management of natural resources. These programs are particularly important in marine systems, where management of recreational and commercial fisheries have historically been contentious. One such program is the California Collaborative Fisheries Research Program (CCFRP), which was designed in 2006 to engage recreational anglers in the scientific process and evaluate the efficacy of California’s network of marine protected areas. CCFRP began on the Central Coast of California and expanded statewide in 2017 to include six partner institutions in three regions: Northern, Central, and Southern California. To date, over 2,000 volunteer anglers have participated in the program, with many anglers volunteering for multiple years. However, the impacts of outreach, education, and collaborative research on those anglers at the statewide scale are currently unknown. Thus, the objective of the current study was to survey the statewide pool of volunteer anglers to assess the degree to which participation in CCFRP has influenced angler perceptions of MPAs, fisheries management, and conservation. We received 259 completed surveys out of a pool of 1,386 active anglers, equating to an 18.7% response rate. Participation in CCFRP resulted in a significant, positive impact on anglers’ attitudes towards MPAs in California across all regions. Anglers who participated in six or more CCFRP fishing trips had a more positive perception of MPAs than those who participated in fewer trips. Volunteer anglers across all regions perceived that they caught larger fishes, a higher abundance of fishes, and a greater diversity of species inside MPAs, consistent with the ecological findings of the program. These results highlight the benefits of involving community members in collaborative scientific research. Collaboration between researchers and the broader community increases transparency and trust between stakeholders, and results in greater understanding of natural resource dynamics, ultimately producing better management outcomes.

State of the California Current Ecosystem report in 2022: a tale of two La Niñas - Andrew R. Thompson; Rasmus Swalethorp; Michaela Alksne; Jarrod A. Santora; Elliott L. Hazen; Andrew Leising; Erin Satterthwaite; William J. Sydeman; Clarissa R. Anderson; Toby D. Auth; Simone Baumann-Pickering; Timothy Baumgardner; et al. (Frontiers in Marine Science, 2024)
2022 marked the third consecutive La Niña and extended the longest consecutive stretch of negative Oceanic Niño Index since 1998-2001. While physical and biological conditions in winter and spring largely adhered to prior La Niña conditions, summer and fall were very different. Similar to past La Niña events, in winter and spring coastal upwelling was either average or above average, temperature average or below average, salinity generally above average. In summer and fall, however, upwelling and temperature were generally average or slightly below average, salinity was close to average and chlorophyll a was close to average. Again, as during prior La Niña events, biomass of northern/southern copepods was above/below average off Oregon in winter, and body size of North Pacific krill in northern California was above average in winter. By contrast, later in the year the abundance of northern krill dropped off Oregon while southern copepods increased and body sizes of North Pacific krill fell in northern California. Off Oregon and Washington abundances of market squid and Pacific pompano (indicators of warm, non-typical La Niña conditions) were high. In the 20 th century, Northern anchovy recruitment tended to be high during cold conditions, but despite mostly warm conditions from 2015-2021 anchovy populations boomed and remained high in 2022. Resident seabird reproductive success, which tended in the past to increase during productive La Niña conditions was highly variable throughout the system as common murre and pelagic cormorant, experienced complete reproductive failure at Yaquina Head, Oregon while Brandt’s cormorant reproduction was average. At three sampling locations off central California, however, common murre reproduction was close to or above average while both pelagic and Brandt’s cormorant were above average. California sealion reproduction has been above average each year since 2016, and pup weight was also above average in 2022, likely in response not to La Niña or El Niño but continuous high abundance of anchovy. The highly variable and often unpredictable physical and biological conditions in 2022 highlight a growing recognition of disconnects between basin-scale indices and local conditions in the CCE. “July-December 2022 is the biggest outlier from individual “strong” La Niña (events) ever going back to the 50s.” – Nate Mantua

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Research priorities for the sustainability of coral-rich western Pacific seascapes - Graeme S. Cumming; Maja Adamska; Michele L. Barnes; Jon Barnett; David R. Bellwood; Joshua E. Cinner; Philippa J. Cohen; Jennifer M. Donelson; Katharina Fabricius; R. Quentin Grafton; Alana Grech; Georgina G. Gurney; et al. (Regional Environmental Change, 2023)
Nearly a billion people depend on tropical seascapes. The need to ensure sustainable use of these vital areas is recognised, as one of 17 policy commitments made by world leaders, in Sustainable Development Goal (SDG) 14 (‘Life below Water’) of the United Nations. SDG 14 seeks to secure marine sustainability by 2030. In a time of increasing social-ecological unpredictability and risk, scientists and policymakers working towards SDG 14 in the Asia–Pacific region need to know: (1) How are seascapes changing? (2) What can global society do about these changes? and (3) How can science and society together achieve sustainable seascape futures? Through a horizon scan, we identified nine emerging research priorities that clarify potential research contributions to marine sustainability in locations with high coral reef abundance. They include research on seascape geological and biological evolution and adaptation; elucidating drivers and mechanisms of change; understanding how seascape functions and services are produced, and how people depend on them; costs, benefits, and trade-offs to people in changing seascapes; improving seascape technologies and practices; learning to govern and manage seascapes for all; sustainable use, justice, and human well-being; bridging communities and epistemologies for innovative, equitable, and scale-crossing solutions; and informing resilient seascape futures through modelling and synthesis. Researchers can contribute to the sustainability of tropical seascapes by co-developing transdisciplinary understandings of people and ecosystems, emphasising the importance of equity and justice, and improving knowledge of key cross-scale and cross-level processes, feedbacks, and thresholds.

Macroalgae exhibit diverse responses to human disturbances on coral reefs - Sara E. Cannon; Simon D. Donner; Angela Liu; Pedro C. González Espinosa; Andrew H. Baird; Julia K. Baum; Andrew G. Bauman; Maria Beger; Cassandra E. Benkwitt; Matthew J. Birt; Yannick Chancerelle; Joshua E. Cinner; et al. (Global Change Biology, 2023)
Scientists and managers rely on indicator taxa such as coral and macroalgal cover to evaluate the effects of human disturbance on coral reefs, often assuming a universally positive relationship between local human disturbance and macroalgae. Despite evidence that macroalgae respond to local stressors in diverse ways, there have been few efforts to evaluate relationships between specific macroalgae taxa and local human‐driven disturbance. Using genus‐level monitoring data from 1205 sites in the Indian and Pacific Oceans, we assess whether macroalgae percent cover correlates with local human disturbance while accounting for factors that could obscure or confound relationships. Assessing macroalgae at genus level revealed that no genera were positively correlated with all human disturbance metrics. Instead, we found relationships between the division or genera of algae and specific human disturbances that were not detectable when pooling taxa into a single functional category, which is common to many analyses. The convention to use percent cover of macroalgae as an indication of local human disturbance therefore likely obscures signatures of local anthropogenic threats to reefs. Our limited understanding of relationships between human disturbance, macroalgae taxa, and their responses to human disturbances impedes the ability to diagnose and respond appropriately to these threats.

Organic matter sulfurization and organic carbon burial in the Mesoproterozoic - Morgan Reed Raven; Peter W. Crockford; Malcolm S.W. Hodgskiss; Timothy W. Lyons; Christopher J. Tino; Samuel M. Webb (Geochimica et Cosmochimica Acta, 2023)

Anthropogenic activity and structures have varying effects on the activity of carnivores in a protected area in Wisconsin, United States - Morgan J. Farmer; Maximilian L. Allen; Erik R. Olson; Julie Van Stappen; Timothy R. Van Deelen (Biodiversity and Conservation, 2022)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Disease surveillance by artificial intelligence links eelgrass wasting disease to ocean warming across latitudes - Lillian R. Aoki; Brendan Rappazzo; Deanna S. Beatty; Lia K. Domke; Ginny L. Eckert; Morgan E. Eisenlord; Olivia J. Graham; Leah Harper; Timothy L. Hawthorne; Margot Hessing‐Lewis; Kevin A. Hovel; Zachary L. Monteith; et al. (Limnology and Oceanography, 2022)
Ocean warming endangers coastal ecosystems through increased risk of infectious disease, yet detection, surveillance, and forecasting of marine diseases remain limited. Eelgrass ( Zostera marina ) meadows provide essential coastal habitat and are vulnerable to a temperature‐sensitive wasting disease caused by the protist Labyrinthula zosterae . We assessed wasting disease sensitivity to warming temperatures across a 3500 km study range by combining long‐term satellite remote sensing of ocean temperature with field surveys from 32 meadows along the Pacific coast of North America in 2019. Between 11% and 99% of plants were infected in individual meadows, with up to 35% of plant tissue damaged. Disease prevalence was 3× higher in locations with warm temperature anomalies in summer, indicating that the risk of wasting disease will increase with climate warming throughout the geographic range for eelgrass. Large‐scale surveys were made possible for the first time by the Eelgrass Lesion Image Segmentation Application, an artificial intelligence (AI) system that quantifies eelgrass wasting disease 5000× faster and with comparable accuracy to a human expert. This study highlights the value of AI in marine biological observing specifically for detecting widespread climate‐driven disease outbreaks.

Evidence of Former Sea Levels from a Passive Seismic Survey at a Sandy Beach; Perranporth, SW England, UK - Andres Payo; Gareth O. Jenkins; Dave Morgan; Nieves G. Valiente; Timothy Scott (Journal of Marine Science and Engineering, 2022)
Since the end of the last glaciation, the United Kingdom’s land surface has been altered by isostatic rebound, rising in the north and sinking in the south. Numerous studies have been published documenting the impact of isostatic rebound on relative sea levels. However, due to the difficulties in acquiring evidence to prove former sea levels, locally, these data can be sparse or absent. In this work, we explored the suitability of the passive seismic survey (PSS) method to estimate the contemporaneous beach thickness in coastal environments where there is a high impedance contrast between the beach deposits and the underlying wave-cut platform. We conducted a three-day survey at Perran Beach, Cornwall, collected 149 measurements using PSS, and interpreted the observations supported by auxiliary topographical, geological, and independent geophysical observation in the study area. The study site is a contemporaneous beach mostly composed of sand underlain by a wave-cut platform composed of igneous and sedimentary rock, therefore high impedance contrast with the sandy beach is anticipated. The elevation of the bedrock relative to the topographical elevation suggests that the bedrock elevation is −15 m ± 5 m below the present day mean sea level, which is coherent with the observation of relative sea level rise along the region of the south-west. The present study contributes to our current limited understanding of land and sea level movements by providing further subsurface information to the coastal geological archive of south-west England, a region currently in need of more data to reconstruct land- and sea-level movements.

Nutrient identity modifies the destabilising effects of eutrophication in grasslands - Oliver Carroll; Evan Batzer; Siddharth Bharath; Elizabeth T. Borer; Sofía Campana; Ellen Esch; Yann Hautier; Timothy Ohlert; Eric W. Seabloom; Peter B. Adler; Jonathan D. Bakker; Lori Biederman; et al. (Ecology Letters, 2022)
Nutrient enrichment can simultaneously increase and destabilise plant biomass production, with co‐limitation by multiple nutrients potentially intensifying these effects. Here, we test how factorial additions of nitrogen (N), phosphorus (P) and potassium with essential nutrients (K+) affect the stability (mean/standard deviation) of aboveground biomass in 34 grasslands over 7 years. Destabilisation with fertilisation was prevalent but was driven by single nutrients, not synergistic nutrient interactions. On average, N‐based treatments increased mean biomass production by 21–51% but increased its standard deviation by 40–68% and so consistently reduced stability. Adding P increased interannual variability and reduced stability without altering mean biomass, while K+ had no general effects. Declines in stability were largest in the most nutrient‐limited grasslands, or where nutrients reduced species richness or intensified species synchrony. We show that nutrients can differentially impact the stability of biomass production, with N and P in particular disproportionately increasing its interannual variability.

Corrigendum: State of the California Current 2019–2020: Back to the Future With Marine Heatwaves? - Edward D. Weber; Toby D. Auth; Simone Baumann-Pickering; Timothy R. Baumgartner; Eric P. Bjorkstedt; Steven J. Bograd; Brian J. Burke; José L. Cadena-Ramírez; Elizabeth A. Daly; Martin de la Cruz; Heidi Dewar; John C. Field; et al. (Frontiers in Marine Science, 2022)

Temporal rarity is a better predictor of local extinction risk than spatial rarity - Peter A. Wilfahrt; Ashley L. Asmus; Eric W. Seabloom; Jeremiah A. Henning; Peter Adler; Carlos A. Arnillas; Jonathan D. Bakker; Lori Biederman; Lars A. Brudvig; Marc Cadotte; Pedro Daleo; Anu Eskelinen; et al. (Ecology, 2021)
Spatial rarity is often used to predict extinction risk, but rarity can also occur temporally. Perhaps more relevant in the context of global change is whether a species is core to a community (persistent) or transient (intermittently present), with transient species often susceptible to human activities that reduce niche space. Using 5–12 yr of data on 1,447 plant species from 49 grasslands on five continents, we show that local abundance and species persistence under ambient conditions are both effective predictors of local extinction risk following experimental exclusion of grazers or addition of nutrients; persistence was a more powerful predictor than local abundance. While perturbations increased the risk of exclusion for low persistence and abundance species, transient but abundant species were also highly likely to be excluded from a perturbed plot relative to ambient conditions. Moreover, low persistence and low abundance species that were not excluded from perturbed plots tended to have a modest increase in abundance following perturbance. Last, even core species with high abundances had large decreases in persistence and increased losses in perturbed plots, threatening the long‐term stability of these grasslands. Our results demonstrate that expanding the concept of rarity to include temporal dynamics, in addition to local abundance, more effectively predicts extinction risk in response to environmental change than either rarity axis predicts alone.

Species loss due to nutrient addition increases with spatial scale in global grasslands - Eric W. Seabloom; Evan Batzer; Jonathan M. Chase; W. Stanley Harpole; Peter B. Adler; Sumanta Bagchi; Jonathan D. Bakker; Isabel C. Barrio; Lori Biederman; Elizabeth H. Boughton; Miguel N. Bugalho; Maria C. Caldeira; et al. (Ecology Letters, 2021)
The effects of altered nutrient supplies and herbivore density on species diversity vary with spatial scale, because coexistence mechanisms are scale dependent. This scale dependence may alter the shape of the species–area relationship (SAR), which can be described by changes in species richness ( S ) as a power function of the sample area ( A ): S = cA z , where c and z are constants. We analysed the effects of experimental manipulations of nutrient supply and herbivore density on species richness across a range of scales (0.01–75 m 2 ) at 30 grasslands in 10 countries. We found that nutrient addition reduced the number of species that could co‐occur locally, indicated by the SAR intercepts (log c ), but did not affect the SAR slopes ( z ). As a result, proportional species loss due to nutrient enrichment was largely unchanged across sampling scales, whereas total species loss increased over threefold across our range of sampling scales.

Angioplasty Induced Changes in Dialysis Vascular Access Compliance - Yihao Zheng; Brian J. Thelen; Nirmala Rajaram; Venkataramu N. Krishnamurthy; James Hamilton; Miguel Angel Funes-Lora; Timothy Morgan; Lenar Yessayan; Brandie Bishop; Nickolas Osborne; Peter Henke; Albert J. Shih; et al. (Annals of Biomedical Engineering, 2021)

State of the California Current 2019–2020: Back to the Future With Marine Heatwaves? - Edward D. Weber; Toby D. Auth; Simone Baumann-Pickering; Timothy R. Baumgartner; Eric P. Bjorkstedt; Steven J. Bograd; Brian J. Burke; José L. Cadena-Ramírez; Elizabeth A. Daly; Martin de la Cruz; Heidi Dewar; John C. Field; et al. (Frontiers in Marine Science, 2021)
The California Current System (CCS) has experienced large fluctuations in environmental conditions in recent years that have dramatically affected the biological community. Here we synthesize remotely sensed, hydrographic, and biological survey data from throughout the CCS in 2019–2020 to evaluate how recent changes in environmental conditions have affected community dynamics at multiple trophic levels. A marine heatwave formed in the north Pacific in 2019 and reached the second greatest area ever recorded by the end of summer 2020. However, high atmospheric pressure in early 2020 drove relatively strong Ekman-driven coastal upwelling in the northern portion of the CCS and warm temperature anomalies remained far offshore. Upwelling and cooler temperatures in the northern CCS created relatively productive conditions in which the biomass of lipid-rich copepod species increased, adult krill size increased, and several seabird species experienced positive reproductive success. Despite these conditions, the composition of the fish community in the northern CCS remained a mixture of both warm- and cool-water-associated species. In the southern CCS, ocean temperatures remained above average for the seventh consecutive year. Abundances of juvenile fish species associated with productive conditions were relatively low, and the ichthyoplankton community was dominated by a mixture of oceanic warm-water and cosmopolitan species. Seabird species associated with warm water also occurred at greater densities than cool-water species in the southern CCS. The population of northern anchovy, which has been resurgent since 2017, continued to provide an important forage base for piscivorous fishes, offshore colonies of seabirds, and marine mammals throughout the CCS. Coastal upwelling in the north, and a longer-term trend in warming in the south, appeared to be controlling the community to a much greater extent than the marine heatwave itself.

CBD Suppression of EAE Is Correlated with Early Inhibition of Splenic IFN-γ + CD8+ T Cells and Modest Inhibition of Neuroinflammation - James M. Nichols; Evangel Kummari; Jessica Sherman; Eun-Ju Yang; Saphala Dhital; Christa Gilfeather; Gabriella Yray; Timothy Morgan; Barbara L. F. Kaplan (Journal of Neuroimmune Pharmacology, 2021)

Longitudinal trends of the small mammal community of the Apostle Islands archipelago - Elyse C. Mallinger; Bijit Khadka; Morgan J. Farmer; Megan Morrison; Julie Van Stappen; Timothy R. Van Deelen; Erik R. Olson (Community Ecology, 2021)

Increasing effects of chronic nutrient enrichment on plant diversity loss and ecosystem productivity over time - Eric W. Seabloom; Peter B. Adler; Juan Alberti; Lori Biederman; Yvonne M. Buckley; Marc W. Cadotte; Scott L. Collins; Laura Dee; Philip A. Fay; Jennifer Firn; Nicole Hagenah; W. Stanley Harpole; et al. (Ecology, 2021)
Human activities are enriching many of Earth’s ecosystems with biologically limiting mineral nutrients such as nitrogen (N) and phosphorus (P). In grasslands, this enrichment generally reduces plant diversity and increases productivity. The widely demonstrated positive effect of diversity on productivity suggests a potential negative feedback, whereby nutrient‐induced declines in diversity reduce the initial gains in productivity arising from nutrient enrichment. In addition, plant productivity and diversity can be inhibited by accumulations of dead biomass, which may be altered by nutrient enrichment. Over longer time frames, nutrient addition may increase soil fertility by increasing soil organic matter and nutrient pools. We examined the effects of 5–11 yr of nutrient addition at 47 grasslands in 12 countries. Nutrient enrichment increased aboveground live biomass and reduced plant diversity at nearly all sites, and these effects became stronger over time. We did not find evidence that nutrient‐induced losses of diversity reduced the positive effects of nutrients on biomass; however, nutrient effects on live biomass increased more slowly at sites where litter was also increasing, regardless of plant diversity. This work suggests that short‐term experiments may underestimate the long‐term nutrient enrichment effects on global grassland ecosystems.

Predator presence affects activity patterns but not food consumption or growth of juvenile corkwing wrasse (Symphodus melops) - Tommy Norin; Josefin Sundin; Rachael Morgan; Anna H. Andreassen; Mirjam Amcoff; Ben Speers-Roesch; Fredrik Jutfelt; Sandra A. Binning; Dominique G. Roche; Timothy D. Clark (Behavioral Ecology and Sociobiology, 2021)

Identifying transformational space for transdisciplinarity: using art to access the hidden third - Toddi A. Steelman; Evan Andrews; Sarah Baines; Lalita Bharadwaj; Emilie Rose Bjornson; Lori Bradford; Kendrick Cardinal; Gary Carriere; Jennifer Fresque-Baxter; Timothy D. Jardine; Ingrid MacColl; Stuart Macmillan; et al. (Sustainability Science, 2019)

Ocean Drilling Perspectives on Meteorite Impacts - Chistopher Lowery; Joanna Morgan; Sean Gulick; Timothy Bralower; Gail Christeson (Oceanography, 2019)

Biocultural diversity and food sovereignty: a case study of human-plant relations in northwestern Ethiopia - Morgan L. Ruelle; Karim-Aly Kassam; Stephen J. Morreale; Zemede Asfaw; Alison G. Power; Timothy J. Fahey (Food Security, 2019)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Subduction initiation and ophiolite crust: new insights from IODP drilling - Mark K. Reagan; Julian A. Pearce; Katerina Petronotis; Renat R. Almeev; Aaron J. Avery; Claire Carvallo; Timothy Chapman; Gail L. Christeson; Eric C. Ferré; Marguerite Godard; Daniel E. Heaton; Maria Kirchenbaur; et al. (International Geology Review, 2017)

Global warming may disproportionately affect larger adults in a predatory coral reef fish - Vanessa Messmer; Morgan S. Pratchett; Andrew S. Hoey; Andrew J. Tobin; Darren J. Coker; Steven J. Cooke; Timothy D. Clark (Global Change Biology, 2017)
Global warming is expected to reduce body sizes of ectothermic animals. Although the underlying mechanisms of size reductions remain poorly understood, effects appear stronger at latitudinal extremes (poles and tropics) and in aquatic rather than terrestrial systems. To shed light on this phenomenon, we examined the size dependence of critical thermal maxima ( CT max) and aerobic metabolism in a commercially important tropical reef fish, the leopard coral grouper ( Plectropomus leopardus ) following acclimation to current‐day (28.5 °C) vs. projected end‐of‐century (33 °C) summer temperatures for the northern Great Barrier Reef ( GBR ). CT max declined from 38.3 to 37.5 °C with increasing body mass in adult fish (0.45–2.82 kg), indicating that larger individuals are more thermally sensitive than smaller conspecifics. This may be explained by a restricted capacity for large fish to increase mass‐specific maximum metabolic rate ( MMR ) at 33 °C compared with 28.5 °C. Indeed, temperature influenced the relationship between metabolism and body mass (0.02–2.38 kg), whereby the scaling exponent for MMR increased from 0.74 ± 0.02 at 28.5 °C to 0.79 ± 0.01 at 33 °C, and the corresponding exponents for standard metabolic rate ( SMR ) were 0.75 ± 0.04 and 0.80 ± 0.03. The increase in metabolic scaling exponents at higher temperatures suggests that energy budgets may be disproportionately impacted in larger fish and contribute to reduced maximum adult size. Such climate‐induced reductions in body size would have important ramifications for fisheries productivity, but are also likely to have knock‐on effects for trophodynamics and functioning of ecosystems.

Expression of the retinoic acid catabolic enzyme CYP26B1 in the human brain to maintain signaling homeostasis - Patrick N. Stoney; Yara D. Fragoso; Reem Bu Saeed; Anna Ashton; Timothy Goodman; Claire Simons; Mohamed S. Gomaa; Angelo Sementilli; Leonardo Sementilli; Alexander W. Ross; Peter J. Morgan; Peter J. McCaffery (Brain Structure and Function, 2016)

Flammability of the keystone savanna bunchgrass Aristida stricta - Jennifer M. Fill; Brett M. Moule; J. Morgan Varner; Timothy A. Mousseau (Plant Ecology, 2016)

The Collaborative Cross as a Resource for Modeling Human Disease: CC011/Unc, a New Mouse Model for Spontaneous Colitis - Allison R. Rogala; Andrew P. Morgan; Alexis M. Christensen; Terry J. Gooch; Timothy A. Bell; Darla R. Miller; Virginia L. Godfrey; Fernando Pardo-Manuel de Villena (Mammalian Genome, 2014)

Functional evaluation of therapeutic response for a mouse model of medulloblastoma - Aislynn K. Samano; Sachiko Ohshima-Hosoyama; Thomas G. Whitney; Suresh I. Prajapati; Aoife Kilcoyne; Eri Taniguchi; William W. Morgan; Laura D. Nelon; Ai-Ling Lin; Osamu Togao; Inkyung Jung; Brian P. Rubin; et al. (Transgenic Research, 2010)

Chlorobaculum tepidum regulates chlorosome structure and function in response to temperature and electron donor availability - Rachael M. Morgan-Kiss; Leong-Keat Chan; Shannon Modla; Timothy S. Weber; Mark Warner; Kirk J. Czymmek; Thomas E. Hanson (Photosynthesis Research, 2009)

Ligand up-regulation does not correlate with a role for CCR1 in pathogenesis in a mouse model of non-lymphocyte-mediated neurological disease - Meryll E. Corbin; Susan Pourciau; Timothy W. Morgan; Marc Boudreaux; Karin E. Peterson (Journal of NeuroVirology, 2006)

Timber-Processing Capacity and Capabilities in the Western United States - Charles E. Keegan; Todd A. Morgan; Krista M. Gebert; Jason P. Brandt; Keith A. Blatner; Timothy P. Spoelma (Journal of Forestry, 2006)
This examination of milling capacity and timber use in the western United States summarizes changes in the region’s wood products industry and its ability to use trees of various sizes. Between 1986 and 2003, total timber-processing capacity in the West (excluding pulpwood and fuelwood) declined from 5.0 to 3.2 billion cubic feet annually, and capacity utilization decreased from 3.6 to 2.5 billion cubic feet. During 2003, 2.2 billion cubic feet of timber processed in the West was from trees ≥10-in. dbh, and 2.5 billion cubic feet (80%) of capacity was not capable of efficiently processing trees <10-in. dbh. Geographic distribution of existing capacity and small-tree capabilities is critical to forest management activities throughout the West.

Geology of the Atlantis Massif (Mid-Atlantic Ridge, 30° N): Implications for the evolution of an ultramafic oceanic core complex - Donna K. Blackman; Jeffrey A. Karson; Deborah S. Kelley; Johnson R. Cann; Gretchen L. Früh-Green; Jeffrey S. Gee; Stephen D. Hurst; Barbara E. John; Jennifer Morgan; Scott L. Nooner; D. Kent Ross; Timothy J. Schroeder; et al. (Marine Geophysical Research, 2002)

A conceptual framework for the study of human ecosystems in urban areas - Steward T. A. Pickett; William R. Burch; Shawn E. Dalton; Timothy W. Foresman; J. Morgan Grove; Rowan Rowntree (Urban Ecosystems, 1997)